Equality and the British Left : A study in progressive political thought, 1900-64 - Jackson, Ben (Book collections on Project MUSE., 2014)
The demand for equality has been at the heart of the politics of the Left in the twentieth century, but what did theorists and politicians on the British Left mean when they said they were committed to 'equality'? How did they argue for a more egalitarian society? Which policies did they think could best advance their egalitarian ideals? Equality and the British Left provides the first comprehensive answers to these questions. It charts debates about equality from the progressive liberalism and socialism of the early twentieth century to the arrival of the New Left and revisionist social democ.